Competição tributária internacional por investimentos estrangeiros diretos – IED: o posicionamento do brasil frente às recomendações da ocde para evitar práticas abusivas - D’Ávila, Lucimara dos Santos (2016)
The purpose of this research is to develop a theoretical material, dealing with the new directions of the international tax policy, in the post-World War II period and after the establishment of the OECD, specifically about the control of tax competition. Aiming to create common interests between countries and thus avoid new conflicts, the OECD stimulated the free international capital flows, including foreign direct investment – FDI. The OECD, however, in order to avoid abusive practices of international tax competition for FDI funding, has instituted since 1998, policies and recommendations suggesting a policy of greater transparency and exchange of tax information between countries. In this scenario, although Brazil is not an OECD member, but a relevant foreign investment recipient, is gradually adapting its tax legislation, seeking to adapt to the best tax practices recommended by the OECD, however there are still many challenges to be faced, as we shall see in this study. This thesis, the final product of this research, intends to be an essentially informative material, but that brings to its readers an objective view of the need for greater fiscal transparency and the adoption of best tax practices recommended by the OECD, towards a fairer tax competition among countries. It is also analyzed the tax legal changes that have occurred in Brazil as part of this global phenomenon, reflecting the specific nature of our reality. The concepts used in the research were subsidized by surveys on secondary sources, including literature, based on books, journals, dissertations or theses presented at universities, sites about these concepts, in addition to the researcher learning in the Doctorate courses